The German Chambers of Commerce and Industry Self-governance, Service, the General Representation of Interests and the Dual System of Professional Education - Sasse, Eberhard; Habisch, Andre; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This open access book examines a particular factor in the enduring international success of German companies. Beyond industrial specialization, peaceful labor relations, local financial markets and the (3z(Bmiracle of the Mittelstand(3y(B, it focuses on a characteristic aspect of governance within the German economy: The Chambers of commerce and industry. Important characteristics of the Chamber system are emphasized - including obligatory membership for firms as well as participatory rules of their self-administration. In turn, the book examines the institution$1 (Bs self-governance, its services, and its mission regarding the general representation of interests. Moreover, the book also identifies the advancement of the dual system of professional education as a central element of the Chamber system. Following an introduction about how the Chamber system works, interviews, case studies and historical explanations help to exemplify the true spirit inherent to this form of representation. In particular, they reveal the essence of how the Chambers contribute to the global success of German companies and foster their corporate responsibility in a practical way. Given its scope, the book will be of particular interest to professionals, policymakers and researchers concerned with how institutional organization can support commerce and industry for the public good. The book was developed in collaboration with Laura Sasse and the Practical Wisdom Society.s
The Magic of Economic Growth -- The Bridge Between Business and Politics - the CCI and Their Normative Foundations -- Comparing the Chamber Systems - What a Colourful World -- The Berman Chambers of Commerce Abroad - An International Win-Win Situation -- CCI in Practice - Public Tasks Delegated by the State -- CCI in Practice - Promoting Business -- CCI in Practice - General Representation of Interests -- The Honorable Merchant - Foundations and Guidelines Steering all CCI Work.
Keywords: Industrial organization; Business ethics; Entrepreneurship; New business enterprises; Economic development; International business enterprises; Industrial Organization; Business Ethics; Entrepreneurship; Economic Growth; International Business